Effects of an oral health program: Community-based education among mothers of young children living in socioeconomically disadvantaged neighborhoods - Zeliha Asli Öcek; Ece Eden; Ummahan Yücel; Meltem Çiçeklioglu (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: An oral health program for mothers starting from pregnancy in a disadvantaged district of İzmir was performed in 2013-2016. Dental behaviors and their determinants among intervention and control groups were compared in the third phase of the program. METHODS: This nonrandomized-controlled study was conducted in Phase 3. The intervention group began with 248 pregnant women; 69.4% (n = 172) of mothers with 6-9-month-old babies participated in Phase 2, 2014. At Phase 3 (18-24 months), 68.6% (n = 118) of mothers in the intervention group and 113 mothers living in another district as controls were included. Sociodemographic characteristics, determinants of behaviors, and outcomes defined as dental behaviors in the last week were assessed using a questionnaire. RESULTS: Regarding knowledge, perceived severity, and fatalistic beliefs, the intervention group had higher correct answer percentages. The percentage of mothers who could clean their children's teeth before sleep was higher in the intervention group (76.3%; P < 0.05), but the difference was lost by a child's resistance. The significant difference on avoiding bedtime nursing (65.3%) and sugary snacks (74.4%) in the intervention group disappeared with the obstacle of a child's protests or interference from relatives. In the intervention group, 32.2% of the mothers reported that they did not give any sugary snacks, 43.2% had never fed during sleep, and 26.3% cleaned their children's teeth during the last week. The results in the control group were 24.8%, 18.6%, and 8.8%, respectively (P <0.05). CONCLUSIONS: The program improved the mothers' views regarding the determinants of dental behaviors, but greater support against obstacles was needed. Social environmental support is planned for the following stages of the program.